Corpus des amphores romaines produites dans les centres de mer Noire : collections des musées de la côte turque de la mer Noire (Eregli, Amasra, Sinop, Samsun, Giresun, Ordu, Trabzon et Amasya) - Tezgör, Dominique Kassab, (Archaeopress Roman archaeology ;, 2020)
The Black Sea cities of Turkey's northern coast - Eregli, Amasra, Sinop, Samsun, Giresun, Ordu, and others - feature museums holding important collections of amphorae. Their state of preservation is exceptional since the majority were recovered intact from the sea. This volume brings them together for analysis in light of recent investigations.